CNTs decorated Cu-BTC with catalytic effect for high-stability lithium-sulfur batteries. Issue 3 (1st February 2022) - Deng, Teng; Men, Xin-Liang; Jiao, Xue-Chao; Wang, Juan
Abstract: Lithium-sulfur (Li–S) batteries have received widespread attention for the reason that their specific capacity is dramatically higher than that of current lithium-ion batteries. However, Li–S batteries still have problems such as poor conductivity, severe "shuttle effect", huge volume changes in the cathode, and lithium dendrites. Here, we report the introduction of carbon nanotubes (CNTs) into metal-organic frameworks (MOFs)-Cu-BTC and obtained Cu-BTC/CNTs with a three-dimensional structure by hydrothermal method. This structure solves the problem of inefficient electrochemical performance caused by poor conductivity when using Cu-BTC to adsorb lithium polysulfides (LiPSs). At the same time, the abundant porous structure is capable of effectively alleviating the volume expansion of the cathode during the reaction process. More importantly, Cu-BTC/CNTs catalyzes redox reactions, greatly improves the catalytic effect of Cu-BTC on LiPSs and the utilization of sulfur. As a result, The Cu-BTC/CNTs/S as sulfur host in the Li–S batteries cathode delivers an initial discharge of 924.69 mAh/g at 0.2C. Even at a high rate of 1C, it also exhibits a specific capacity of 805.28 mAh/g and still maintains 406.68mAh/g after 200 cycles at 1C. The above results indicate that the introduction of CNTs not only improves the overall conductivity of the material but also can fully exert the catalytic effect of Cu-BTC on the conversion of LiPSs. This work provides a convenient strategy to promote the conversion of LiPSs along with improving the catalytic activity of MOFs in Li–S batteries.